Anti-glare laminate

By controlling the relationship between haze and ten-point average roughness in the anti-glare laminate of the liquid crystal display device, the glare problem caused by the concave and convex shape is solved, and the effect of reducing glare and improving display performance is achieved.

CN119790326APending Publication Date: 2025-04-08MITSUBISHI GAS CHEM CO INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060490.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When an anti-glare film is assembled on the surface of the liquid crystal display device, the lens effect of the concave and convex shape causes the pixel to be enlarged, resulting in glare, and affecting the display performance.

Method used

By setting the base material layer and the anti-glare layer in the anti-glare laminate, and controlling the relationship between the haze (H) of the anti-glare layer and the ten-point average roughness (Rzjis) is achieved, the condition of H/Rzjis ≥4.0 is satisfied to suppress glare.

Benefits of technology

It realizes reducing glare, improving the recognition of the display device, and ensuring high-fine pixel display performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005275643470000061
    Figure BDA0005275643470000061
  • Figure BDA0005275643470000062
    Figure BDA0005275643470000062
  • Figure BDA0005275643470000071
    Figure BDA0005275643470000071
Patent Text Reader

Abstract

According to the present invention, provided is an anti-glare laminate comprising at least a base material layer and an anti-glare layer, the haze (H) of the anti-glare laminate and the ten-point average roughness (Rzjis) of the anti-glare layer measured with a reference length of 0.8 mm satisfy the following formula (1): H / Rzjis > = 4.0 (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anti-glare laminate. More specifically, the present invention relates to an anti-glare laminate having both anti-glare performance and high scratch resistance and substrate adhesion, and is used as a surface material for a vehicle-mounted liquid crystal display device or a mobile phone terminal, a personal computer, or a tablet PC, which has excellent anti-glare performance. Background Art

[0002] In a liquid crystal display device, an optical laminate for preventing reflection is usually provided on the outermost surface. This anti-reflection optical laminate suppresses image reflection or reduces reflectivity by scattering and interfering light.

[0003] As one of the optical laminates for anti-reflection, an anti-glare film having an anti-glare layer with a concavo-convex shape formed on the surface of a transparent substrate is known. This anti-glare film can scatter external light by utilizing the concavo-convex shape of the surface, thereby preventing the reduction of visibility caused by the reflection of external light and the reflection of the image. In addition, the optical laminate is usually provided on the outermost surface of the liquid crystal display device, so it is also necessary to give it hard coating properties to prevent damage during operation.

[0004] On the display surface of liquid crystal display devices and organic electroluminescent (EL) display devices, a mixture of fine particles and a binder resin or a curable resin is usually coated on a substrate to form fine concave and convex surfaces to prevent specular reflection and prevent image reflection.

[0005] Patent Document 1 discloses a method of forming unevenness on a surface by using dipentaerythritol hexaacrylate as a multifunctional acrylate and SYLYSIA 350 as silica particles in an antiglare layer.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2009-66891 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] When the surface is uneven, it can prevent the reflection of external light, but it may cause the display performance of the display device to deteriorate. In particular, when an anti-glare film is installed on the surface of a display device with high-definition pixels, the pixels of the display device may appear to be magnified due to the lens effect of the surface unevenness, etc., which may cause so-called glare.

[0011] Therefore, an object of the present invention is to provide an anti-glare laminate that suppresses glare.

[0012] Technical solutions for solving technical problems

[0013] The inventors of the present invention have conducted intensive research to solve the above technical problems and found that the above technical problems can be solved by satisfying a prescribed relationship between the haze (H) of the anti-glare laminate and the ten-point average roughness (Rzjis) of the anti-glare layer. That is, the present invention is as follows.

[0014] <1> An anti-glare laminate comprising at least a substrate layer and an anti-glare layer,

[0015] The haze (H) of the anti-glare laminate and the ten-point average roughness (Rzjis) of the anti-glare layer measured with a reference length of 0.8 mm satisfy the following formula (1).

[0016] H / Rzjis≥4.0 (1)

[0017] <2> The anti-glare laminate according to <1> above, wherein the anti-glare laminate has a haze of 1 to 20%.

[0018] <3> The anti-glare laminate according to <1> or <2>, wherein the anti-glare layer has a ten-point average roughness (Rzjis) of 0.2 to 1.5 μm measured with a reference length of 0.8 mm.

[0019] <4> The anti-glare laminate according to any one of <1> to <3>, wherein the anti-glare layer contains an active energy ray-curable resin and light diffusing fine particles.

[0020] <5> An anti-glare laminate as described in any one of <1> to <4> above, wherein the anti-glare layer contains at least a monomer (A) containing a multifunctional (meth)acryloyl group, a polymer (B) containing a (meth)acryloyl group, a photopolymerization initiator (C) and silica particles (D), the average particle size of the silica particles is 1 to 7 μm, and the oil absorption of the silica particles is 30 to 250 mL / 100 g.

[0021] <6> An anti-glare laminate as described in <5> above, wherein, when the total of the above-mentioned (A) component and the (B) component is set to 100 mass %, the proportion of the (A) component is 40 to 90 mass %, the proportion of the (B) component is 10 to 60 mass %, the double bond equivalent of the above-mentioned (B) component is less than 400 g / mol, and the weight average molecular weight of the above-mentioned (B) component is 5,000 to 10,0000.

[0022] <7> The anti-glare laminate according to <5>, wherein the content of the component (D) is 1 to 20% by mass, assuming that the total of the components (A) and (B) is 100% by mass.

[0023] <8> The anti-glare laminate according to any one of <1> to <7>, wherein the substrate layer includes an aromatic polycarbonate resin layer.

[0024] <9> The anti-glare laminate according to any one of <1> to <8>, wherein the base layer includes at least two layers of an acrylic resin layer and an aromatic polycarbonate resin layer.

[0025] <10> The anti-glare laminate according to any one of <1> to <9>, further comprising an optical interference layer on the anti-glare layer.

[0026] <11> The anti-glare laminate according to any one of <1> to <10>, wherein the substrate layer has an adhesive layer on a surface opposite to the anti-glare layer.

[0027] Effects of the Invention

[0028] According to the present invention, it is possible to provide an anti-glare laminate having reduced glare and excellent visibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 : is a cross-sectional view showing a specific example of an anti-glare laminate according to one embodiment of the present invention. Figure 1 The structure of the anti-glare laminated body 10 of the laminated body exemplified in FIG. 1 is composed of an anti-glare layer 12 , a polymethyl methacrylate layer (PMMA resin layer) 16 , and a polycarbonate layer (PC resin layer) 20 . DETAILED DESCRIPTION

[0030] The present invention will be described in detail below, but the present invention is not limited to the following embodiments, and can be modified arbitrarily within the scope of the invention.

[0031] The anti-glare laminate of the present invention comprises an anti-glare layer and a substrate layer. Each of these layers will be described below.

[0032] [Anti-glare layer]

[0033] The anti-glare layer of the present invention has a concavo-convex shape on the surface. As a material constituting the anti-glare layer, an active energy ray-curable resin is preferably used.

[0034] The method for forming the anti-glare layer is not particularly limited, and the anti-glare layer can be formed, for example, by applying a composition containing an active energy ray-curable resin on a substrate and then curing the composition by irradiating the substrate with active energy rays.

[0035] The method for applying the composition in the present invention is not particularly limited, and known methods can be used. For example, spin coating, dip coating, spraying, slide coating, rod coating, roller coating, gravure coating, die coating, meniscus coating, flexographic printing, screen printing, beat coating, brush coating, etc. can be cited.

[0036] As the active energy ray, for example, ultraviolet rays can be used. As a lamp for irradiating ultraviolet rays, a lamp having a light emission distribution below 420 nm in wavelength can be used, and examples thereof include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, etc. Among them, high-pressure mercury lamps or metal halide lamps can efficiently emit light in the active wavelength range of the initiator, and will not emit a large amount of short-wavelength light that reduces the viscoelastic properties of the obtained polymer due to crosslinking or long-wavelength light that heats and evaporates the reaction composition, and are therefore preferred.

[0037] As a method for forming the concavoconvex on the anti-glare layer, for example, molding using a mold can be cited. The molding using a mold can be produced by the following method: a mold having a shape complementary to the concavoconvex surface is prepared, and ultraviolet curing is performed in a state where the transparent substrate coated with the anti-glare layer is closely attached.

[0038] As the concavoconvex forming method on the anti-glare layer, from the viewpoint of cost, it is preferred to mix light diffusing particles in the anti-glare layer forming composition. As the light diffusing particles, organic particles or inorganic particles can be used, and from the viewpoint of ensuring the hardness of the anti-glare layer, silicon dioxide particles are preferably used.

[0039] Regarding the anti-glare laminate of the present invention, when the haze specified in JIS K 7136 is set to H and the ten-point average roughness of the anti-glare layer surface with a reference length of 0.8 mm specified in JIS B 0601-2001 is set to Rzjis, it is necessary to satisfy H / Rzjis≥4.0, preferably 20.0≥H / Rzjis≥4.0, and more preferably 10.0≥H / Rzjis≥4.5.

[0040] In the present invention, the haze of the antiglare laminate and the ten-point average roughness (Rzjis) of the antiglare layer can be measured by the method described in the Examples below.

[0041] As the meaning of the above formula, the larger the Rzjis, the easier it is for the concavo-convex shape of the anti-glare layer surface to interfere with the pixels of the display and produce glare, but if the haze is large enough, the glare is difficult to identify due to the light diffusion effect.

[0042] The haze of the antiglare laminate of the present invention is preferably 1 to 20%, more preferably 3 to 15%.

[0043] On the other hand, the ten-point average roughness (Rzjis) of the antiglare layer of the present invention measured with a reference length of 0.8 mm is preferably 0.2 to 1.5 μm, more preferably 0.5 to 1.0 μm.

[0044] Anti-glare layer of the present invention is preferably composed of a composition containing a monomer containing a multifunctional (meth) acryloyl group, a polymer containing a (meth) acryloyl group, a photopolymerization initiator and silicon dioxide particles. In order to improve the function of the anti-glare layer, various additives can also be contained. Below, the composition preferably contained in the composition used as the raw material of the anti-glare layer is described.

[0045] <Polyfunctional (meth)acryloyl group-containing monomer>

[0046] The anti-glare layer preferably contains a monomer containing a polyfunctional (meth)acryloyl group. The polyfunctional (meth)acryloyl group-containing monomer is cross-linked by polymerization, thereby increasing the hardness of the anti-glare layer.

[0047] In the present invention, the polyfunctional (meth)acryloyl group-containing monomer refers to a compound having two or more (meth)acryloyl groups. The polyfunctional (meth)acryloyl group-containing monomer may be used alone or in combination of two or more.

[0048] Examples of the polyfunctional (meth)acryloyl group-containing monomer include 1,6-hexanediol (meth)acrylate, 1,9-nonanediol (meth)acrylate, bisphenol A di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0049] The polyfunctional (meth)acryloyl group-containing monomer may be modified with an oxyalkylene group or an epoxy group. By performing the oxyalkylene group modification or the epoxy group modification, the curing shrinkage during crosslinking can be suppressed and the heat resistance of the anti-glare layer can be improved.

[0050] The molecular weight of the polyfunctional (meth)acryloyl group-containing monomer is preferably 1000 or less, more preferably 800 or less, and further preferably 600 or less. When the molecular weight exceeds 1000, the adhesion to the substrate may be reduced.

[0051] The hydroxyl value of the polyfunctional (meth)acryloyl group-containing monomer is preferably 10 mgKOH / g or more, more preferably 30 mgKOH / g or more, and further preferably 50 mgKOH / g or more. When the hydroxyl value is less than 10 mgKOH / g, the dispersibility of the composition may be reduced.

[0052] When the total amount of the monomer containing a multifunctional (meth) acryloyl group and the polymer containing a (meth) acryloyl group is set to 100% by mass, the amount of the monomer containing a multifunctional (meth) acryloyl group is preferably 40 to 90% by mass, more preferably 50 to 90% by mass, further preferably 55 to 85% by mass, and particularly preferably 60 to 80% by mass. When it is less than 40% by mass, the adhesion between the anti-glare layer and the substrate layer decreases, and when it is greater than 90% by mass, the heat resistance of the anti-glare layer sometimes decreases.

[0053] <(Meth)acryloyl group-containing polymer>

[0054] The anti-glare layer preferably contains a (meth)acryloyl group-containing polymer. The (meth)acryloyl group-containing polymer can suppress curing shrinkage due to polymerization and improve heat resistance.

[0055] For example, by copolymerizing (meth)acrylic acid and (meth)acrylic acid glycidyl ether to synthesize an epoxy compound having a (meth)acrylate skeleton, and then adding acrylic acid or methacrylic acid to the epoxy compound, a (meth)acryloyl group-containing polymer can be obtained. A synthesis example is shown below.

[0056]

[0057] Examples of epoxy (meth)acrylates used for the (meth)acryloyl group-containing polymer include those having a repeating unit represented by the following formula (I).

[0058]

[0059] In formula (I), m is an alkylene group having 1 to 4 carbon atoms or a single bond, n is an alkyl group having 1 to 4 carbon atoms or hydrogen, p is a single bond or an alkylene group having 1 or 2 carbon atoms, and q is an alkyl group having a total carbon number of 1 to 12 or hydrogen which may contain at least one substituent selected from epoxy, hydroxyl, acryloyl and methacryloyl.

[0060] The epoxy (meth)acrylate polymer more preferably comprises the following repeating units: i.e., in the above formula (I), m is an alkylene group having 1 or 2 carbon atoms, n is an alkyl group having 1 or 2 carbon atoms, p is a single bond or a methylene group, and q is a repeating unit of an alkyl group having a total carbon number of 1 to 6 or hydrogen which may contain at least one substituent selected from glycidyl, hydroxyl and acryloyl groups.

[0061] For example, in the above formula (I), m is a methylene group, n is a methyl group, p is a single bond, and q is a methyl group, an alkyl group having 5 or less carbon atoms including a glycidyl group (epoxy group), an alkyl group having 8 or less carbon atoms including a hydroxyl group and an acryloyl group, etc.

[0062] Specific examples of the repeating unit contained in the epoxy (meth)acrylate polymer include repeating units represented by the following formula (II-a), formula (II-b), and formula (II-c).

[0063]

[0064] In the (meth)acrylate polymer, based on the total molar number of the repeating unit of the above formula (II-a), the repeating unit of the above formula (II-b) and the repeating unit of the above formula (II-c), the repeating unit of the above formula (II-a) is preferably 30 to 85 mol%, more preferably 40 to 80 mol%. Based on the above total molar number, the repeating unit of the above formula (II-b) is preferably 5 to 30 mol%, more preferably 10 to 25 mol%. In addition, based on the above total molar number, the repeating unit of the above formula (II-c) is preferably 10 to 40 mol%, more preferably 10 to 35 mol%.

[0065] The molar ratio of the repeating unit of the formula (II-a), the repeating unit of the formula (II-b), and the repeating unit of the formula (II-c) is preferably 4.5 to 5.5:1.5 to 2.5:2.5 to 3.5, for example, 5:2:3.

[0066] Such (meth)acryloyl group-containing polymers are sold as commercial products and can be easily obtained. Examples thereof include SMP-220A (manufactured by Kyoeisha Chemical Co., Ltd.), SMP-250A (manufactured by Kyoeisha Chemical Co., Ltd.), SMP-360A (manufactured by Kyoeisha Chemical Co., Ltd.), SMP-550A (manufactured by Kyoeisha Chemical Co., Ltd.), HA7975 (manufactured by Showa Denko Materials Co., Ltd.), HA7975D (manufactured by Showa Denko Materials Co., Ltd.), RA-4101 (manufactured by Negami Industry Co., Ltd.), 8KX-078 (manufactured by Daisei Fine Chemicals Co., Ltd.), and 8KX-212 (manufactured by Daisei Fine Chemicals Co., Ltd.).

[0067] The double bond equivalent of the (meth)acryloyl group-containing polymer is preferably 400 g / mol or less, more preferably 360 g / mol or less, and particularly preferably 250 g / mol or less. If it is greater than 400 g / mol, the hardness of the antiglare layer may decrease.

[0068] The weight average molecular weight of the (meth)acryloyl group-containing polymer is preferably 5,000 to 100,000, more preferably 10,000 to 70,000, and even more preferably 15,000 to 50,000. If it is less than 5,000, the effect of suppressing cure shrinkage may not be obtained, and if it exceeds 100,000, the viscosity of the composition may increase, making coating difficult.

[0069] When the total amount of the multifunctional (meth)acryloyl-containing monomer and the (meth)acryloyl-containing polymer is set to 100 mass %, the amount of the (meth)acryloyl-containing polymer is preferably 10 to 60 mass %, more preferably 10 to 50 mass %, further preferably 15 to 45 mass %, and particularly preferably 20 to 40 mass %. When it is less than 10 mass %, the heat resistance of the anti-glare layer decreases, and when it is greater than 60 mass %, the adhesion between the anti-glare layer and the substrate layer may decrease.

[0070] The anti-glare layer preferably contains silica particles. The silica particles form irregularities on the surface of the anti-glare layer, thereby producing an anti-glare effect.

[0071] Examples of the method for producing silica particles include a dry method and a wet method. Among these, the wet method is preferred from the viewpoint of a large number of silanol groups on the surface and good dispersibility with resins.

[0072] The shape of the silica particles is not particularly limited, and examples thereof include spherical shapes and irregular shapes. Irregular shapes are more preferred because they can adhere firmly to the resin and improve the scratch resistance of the antiglare layer.

[0073] The average particle size of the silica particles is preferably 1 to 7 μm, more preferably 2 to 6 μm, and particularly preferably 3 to 5 μm. When the particle size is less than 1 μm, the anti-glare effect cannot be obtained, and when the particle size is greater than 7 μm, glare is easily generated. In the present invention, the average particle size of the silica particles can be measured by laser diffraction.

[0074] The oil absorption of the silica particles is preferably 30 to 250 mL / 100 g, more preferably 70 to 230 mL / 100 g, and particularly preferably 90 to 200 mL / 100 g. When the oil absorption is less than 30 mL / 100 g, the dispersibility in the resin decreases, and when the oil absorption is greater than 250 mL / 100 g, glare of the anti-glare layer is likely to occur. In the present invention, the oil absorption of the silica particles can be measured according to JIS K 5101.

[0075] Such silica particles are sold as commercial products and can be easily obtained. Examples thereof include SYLYSIA series, SYLOPHOBIC series, SYLOSPHERE series of Fuji Silicon Chemical Co., Ltd., Nipsil series, NIPGEL series of Tosoh Silicon Chemical Co., Ltd., Sunsphere series of AGC Si-Tech, REOLOSIL series of Tokuyama Co., Ltd., and AEROSIL series of NIPPON AEROSIL CO., LTD.

[0076] When the total amount of the multifunctional (meth) acryloyl-containing monomer and the (meth) acryloyl-containing polymer is 100 mass %, the amount of silica particles is preferably 1 to 20 mass %, more preferably 3 to 18 mass %, and further preferably 5 to 15 mass %. When it is less than 1 mass %, the anti-glare effect may not be obtained, and when it is greater than 20 mass %, the total light transmittance of the anti-glare laminate may decrease or glare may be easily generated.

[0077] The anti-glare layer preferably contains a photopolymerization initiator. As the photopolymerization initiator, Omnirad 184 (1-hydroxy-cyclohexyl-phenyl-ketone), Omnirad 1173 (2-hydroxy-2-methyl-1-phenyl-propane-1-ketone), Omnirad TPO (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide), Omnirad 819 (bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide), EsacureONE (oligo(2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone)) manufactured by IGM Resins BV can be used. Among these, Omnirad 184 and the like are preferably used as the photopolymerization initiator from the viewpoint of heat resistance.

[0078] In the anti-glare layer, based on the total weight of the anti-glare layer, preferably 1% by weight to 6% by weight of a photopolymerization initiator is contained. The content of the photopolymerization initiator in the anti-glare layer is more preferably 2% by weight to 5% by weight, and further preferably 3% by weight to 4% by weight.

[0079] In order to impart scratch resistance and hardness to the anti-glare layer, nanoparticles can be added. For example, nano silicon dioxide, nano aluminum oxide, nano titanium dioxide, nano zirconium oxide, etc. can be used. In addition, as organic particles, nano diamonds, etc. can be used. The nanoparticles contained in the anti-glare layer are preferably treated with a surface treatment agent. Through surface treatment, inorganic nanoparticles can be dispersed in a stable state in a composition, particularly in a polymer containing a (meth)acryloyl group.

[0080] As the surface treatment agent used for the nanoparticles, it is suitable to use a compound having a substituent capable of bonding to the surface of the nanoparticles and a substituent having high compatibility with the components of the hard coating composition for dispersing the nanoparticles, particularly a polymer containing a (meth)acryloyl group. For example, as the surface treatment agent, silane compounds, alcohols, amines, carboxylic acids, sulfonic acids, phosphonic acids, etc. can be used.

[0081] The nanoparticles preferably have copolymerizable groups on their surfaces. The copolymerizable groups can be introduced by surface treatment of the inorganic nanoparticles, and specific examples of the copolymerizable groups include vinyl groups, meth(acrylic acid) groups, free radical polymerizable groups, and the like.

[0082] The average particle size of the nanoparticles is preferably 5 to 500 nm, more preferably 10 to 300 nm, and even more preferably 20 to 100 nm. The average particle size of the nanoparticles is measured, for example, using a Zetasizer Nano ZS from Malvern Panalytical by a particle size measurement method using a dynamic light scattering method.

[0083] As commercially available products of nanoparticles, for example, SNOWTEX series and organosilica sol series manufactured by Nissan Chemical Co., Ltd. and ADMANANO series manufactured by ADMATECHS COMPANY LIMITED can be used.

[0084] In order to impart leveling, antifouling and abrasion resistance to the antiglare layer, an organosilicon compound may be added. The organosilicon compound preferably uses a compound having a polyalkylsiloxane bond. These compounds may also be synthesized products, and commercial products may be easily obtained. For example, the KP series of Shin-Etsu Silicone Co., Ltd., the BYK series of BYK Chemical Japan Co., Ltd., and the TEGO Glide series of EVONIK may be used.

[0085] In order to impart leveling, antifouling and abrasion resistance to the antiglare layer, a fluorine compound may be added. The fluorine compound preferably uses a compound having a perfluoropolyether bond. These compounds may also be synthesized products, and commercial products may be easily obtained. For example, the MEGAFACE RS series of DIC Corporation, the KY series of Shin-Etsu Chemical Co., Ltd., the OPTOOL series of Daikin Co., Ltd., etc. may be used.

[0086] In order to impart weather resistance to the antiglare layer, an ultraviolet absorber may be added. Examples of the ultraviolet absorber include benzophenone-based ultraviolet absorbers such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, 2-hydroxy-4-octadecyloxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and 2,2',4,4'-tetrahydroxybenzophenone, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)benzotriazole, and 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)benzotriazole. benzotriazole-based UV absorbers such as benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, benzoate-based UV absorbers such as phenyl salicylate and 2,4-di-tert-butylphenyl-3,5-di-tert-butyl-4-hydroxybenzoate, 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, triazine-based ultraviolet absorbers such as 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]ethyl methacrylate, ... 3-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl methacrylate, 3-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl methacrylate, 4-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl methacrylate, 4-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl acrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl acrylate,2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yloxy]ethyl acrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yloxy]ethyl acrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl methacrylate, ]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl acrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]butyl methacrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]butyl methacrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl acrylate, 2-(methacryloyloxy)ethyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl acrylate, Sesamol-type benzotriazole ultraviolet absorbers such as 2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 4-(methacryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, and 4-(acryloyloxy)butyl-2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate. The content of the ultraviolet absorber in the antiglare layer is preferably 0 to 5% by mass, more preferably 0 to 3% by mass, and even more preferably 0 to 1% by mass. When it is more than 5% by mass, UV curing may be inhibited.

[0087] In order to impart weather resistance to the antiglare layer, a light stabilizer may be added. Examples of the light stabilizer include hindered amine light stabilizers such as bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethylpiperidin-4-yl) sebacate, bis(1-undecanyloxy-2,2,6,6,-tetramethylpiperidin-4-yl) carbonate, 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate, bis[2,2,6,6-tetramethyl-1-(octyloxy)piperidin-4-yl] sebacate, and bis[1,2,2,6,6-pentamethyl-4-piperidinyl] 2-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]-2-butylmalonate. The content of the photostabilizer in the antiglare layer is preferably 0 to 5% by mass, more preferably 0 to 3% by mass, and even more preferably 0 to 1% by mass. When the content is more than 5% by mass, UV curing may be inhibited.

[0088] The diluent solvent used in preparing the anti-glare layer forming composition is used to adjust the viscosity and is not particularly limited as long as it is non-polymerizable. With such a diluent solvent, the anti-glare layer forming composition can be easily coated mainly on the transparent substrate layer.

[0089] Examples of the diluting solvent include toluene, xylene, ethyl acetate, propyl acetate, butyl acetate, methyl cellosolve, ethyl cellosolve, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, methanol, ethanol, isopropanol, butanol, diacetone alcohol, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, hexane, heptane, octane, decane, dodecane, propylene glycol monomethyl ether, and 3-methoxybutanol.

[0090] As a method for coating the anti-glare layer-forming composition on the base layer, bar coating, gravure coating, die coating, dip coating, spray coating, etc. can be used.

[0091] After the composition is applied, it is dried at a predetermined temperature. The drying temperature is preferably 30 to 150° C., more preferably 60 to 120° C. When the drying temperature is lower than 30° C., the organic solvent remains, which is likely to affect the physical properties of the anti-glare layer. When the drying temperature is higher than 150° C., the substrate layer may be deformed.

[0092] The thickness of the antiglare layer is preferably in the range of 1 μm to 30 μm, more preferably 2 μm to 20 μm, and further preferably 5 μm to 15 μm. If it is less than 1 μm, it is difficult to obtain the required performance, and if it is greater than 30 μm, there is a possibility of warping or poor flexibility.

[0093] [Base material layer]

[0094] The substrate layer contains a thermoplastic resin. There is no particular limitation on the type of thermoplastic resin, and various resins such as polycarbonate (PC) resin, acrylic resins such as polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyimide (PI), cycloolefin copolymer (COC), norbornene-containing resins, polyether sulfone, celluloid, and aromatic polyamide can be used. Among these options, the thermoplastic resin of the substrate layer preferably contains at least a polycarbonate resin. In addition, from the viewpoint of toughness and heat resistance, it is desirable to use an aromatic polycarbonate.

[0095] The type of polycarbonate resin contained in the substrate layer is not particularly limited as long as it contains a -[O-R-OCO]- unit containing a carbonate bond in the main chain of the molecule (R is a group containing an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and is a group having a linear structure or a branched structure). Polycarbonates having a bisphenol skeleton are preferred, and polycarbonates having a bisphenol A skeleton or a bisphenol C skeleton are particularly preferred. As the polycarbonate resin, a mixture or copolymer of bisphenol A and bisphenol C can be used. By using a bisphenol C-based polycarbonate resin, such as a polycarbonate resin containing only bisphenol C, a mixture or copolymer of bisphenol C and bisphenol A, the hardness of the substrate layer can be increased.

[0096] The viscosity average molecular weight of the polycarbonate resin is preferably 15,000 to 40,000, more preferably 20,000 to 35,000, and even more preferably 22,500 to 25,000.

[0097] In addition, the acrylic resin contained in the substrate layer is not particularly limited, and for example, homopolymers of various (meth) acrylic esters represented by polymethyl methacrylate (PMMA) and methyl methacrylate (MMA), or copolymers of PMMA or MMA with one or more other monomers, and mixtures of these resins can be cited. Among these, (meth) acrylic esters containing cyclic alkyl structures with low birefringence, low hygroscopicity, and excellent heat resistance are preferred. As examples of the above (meth) acrylic resins, there are Acrypet (manufactured by Mitsubishi Rayon Co., Ltd.), DELPET (manufactured by Asahi Kasei Chemicals Co., Ltd.), and Parapet (manufactured by Kuraray Co., Ltd.), but are not limited to these.

[0098] A double-layer product containing a polycarbonate resin and the above-mentioned acrylic resin can also be used. In this case, an anti-glare layer is preferably provided on the acrylic resin side. By using a double-layer product containing a polycarbonate resin and the above-mentioned acrylic resin, the surface hardness can be increased and the toughness of the substrate layer can be maintained.

[0099] In addition, the substrate layer may contain additives as components other than the thermoplastic resin. For example, at least one additive selected from the group consisting of a heat stabilizer, an antioxidant, a flame retardant, a flame retardant aid, an ultraviolet absorber, a release agent, and a colorant. In addition, an antistatic agent, a fluorescent brightener, an antifogging agent, a fluidity improver, a plasticizer, a dispersant, an antibacterial agent, etc. may also be added to the substrate layer.

[0100] The base material layer preferably contains 80% by mass or more of a thermoplastic resin, more preferably 90% by mass or more, and particularly preferably 95% by mass or more of a thermoplastic resin. In addition, the base material layer preferably contains 80% by mass or more of a polycarbonate resin, more preferably 90% by mass or more, and particularly preferably 95% by mass or more of a polycarbonate resin in the thermoplastic resin.

[0101] [Optical interference layer]

[0102] In a preferred embodiment of the present invention, an optical interference layer is provided on the anti-glare layer. The method for forming the optical interference layer is not particularly limited, and coating, vapor deposition, sputtering and other film-forming methods can be used.

[0103] As a material for forming by coating, a coating material containing hollow silica can be used. The thickness of the layer containing hollow silica is preferably 80 to 120 nm.

[0104] When forming the film by vapor deposition or sputtering, a metal oxide can be used. As the metal oxide, SiO2, TiO2, Nb2O5, etc. can be used.

[0105] The low refractive index layer and the high refractive index layer are alternately laminated to form a layer with a film thickness of 200 to 300 nm to obtain an optical interference effect. An adhesion layer such as SiON or SiOx may be provided between the anti-glare layer and the optical interference layer to improve adhesion.

[0106] [Adhesive layer]

[0107] In a preferred embodiment of the present invention, the substrate layer has an adhesive layer on the opposite side of the anti-glare layer. The method for forming the adhesive layer is not particularly limited, and it is preferably formed by a coating method. As the material of the adhesive layer, there is no particular restriction, and acrylic adhesives, silicone adhesives and polyurethane adhesives can be used. The thickness of the adhesive layer is not particularly limited, and is preferably more than 10 μm, more preferably more than 25 μm, further preferably more than 35 μm, and can also be more than 40 μm. In addition, the thickness of the adhesive layer is preferably less than 70 μm, more preferably less than 60 μm. By being within the above range, more appropriate adhesive properties and adhesive strength can be achieved.

[0108] [Protective film]

[0109] After drying, in order to prevent the anti-glare layer from being damaged, a protective film can be pasted on the anti-glare layer. The surface of the protective film in contact with the anti-glare layer has an adhesive surface with appropriate adhesive force, which is bonded to the surface of the anti-glare layer. The protective film can be a single layer with only an adhesive layer, preferably a two-layer structure with a substrate and an adhesive layer. In the protective film of the two-layer structure, the adhesive surface of the adhesive layer is laminated on the anti-glare layer in a manner that contacts the anti-glare layer. The protective film can be a multilayer structure that also includes layers other than the above-mentioned substrate and adhesive layer. In addition, the protective film can also be a single-layer structure, and even in the protective film of the single-layer structure, the adhesive surface as the surface of the anti-glare layer side also has appropriate adhesive force.

[0110] The base material of the protective film is preferably formed of a thermoplastic resin, and more preferably contains a polyolefin resin. As the polyolefin resin contained in the protective film, for example, polyethylene, polypropylene, etc. can be used, and it can be a homopolymer or a copolymer. Among the polyolefin resins, polyethylene is preferred.

[0111] As polyethylene, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), very low-density polyethylene (VLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE) and the like can be used, and low-density polyethylene is preferred.

[0112] In addition, as the polyolefin copolymer, a copolymer of ethylene or propylene and a monomer copolymerizable with these can be used. Examples of the monomer copolymerizable with ethylene or propylene include α-olefins, styrenes, dienes, cyclic compounds, and oxygen-containing compounds.

[0113] As the above-mentioned α-olefins, 1-butene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. can be listed. As the above-mentioned styrenes, styrene, 4-methylstyrene, 4-dimethylaminostyrene, etc. can be listed. As the above-mentioned dienes, 1,3-butadiene, 1,5-hexadiene, 1,4-hexadiene, 1,7-octadiene, etc. can be listed. As the above-mentioned cyclic compounds, norbornene, cyclopentene, etc. can be listed. As compounds containing oxygen atoms, hexenol, hexenoic acid, methyl octenoate, etc. can be listed. These copolymerizable monomers can be used alone or in combination of two or more. It can also be a copolymer of ethylene and propylene.

[0114] The copolymer may be in any form of alternating copolymerization, random copolymerization, or block copolymerization.

[0115] The polyolefin resin contained in the base material of the protective film may also contain a small amount of modified polyolefin resin modified with a carboxyl group-containing monomer such as acrylic acid, maleic acid, methacrylic acid, maleic anhydride, fumaric acid, itaconic acid, etc. The modification can usually be achieved by copolymerization or graft modification.

[0116] The substrate of the protective film preferably contains 80% by weight or more of a polyolefin resin based on the total weight of the substrate, more preferably 90% by weight or more of a polyolefin resin, and even more preferably 95% by weight or more of a polyolefin resin.

[0117] The adhesive layer of the protective film is preferably formed of an elastomer or a thermoplastic resin. As the thermoplastic resin contained in the adhesive layer, polyolefin resins such as polypropylene and modified polyolefin can be cited. As the polyolefin resin contained in the masking film, for example, polyethylene, polypropylene, etc. can be used, which can be a homopolymer or a copolymer. Among the polyolefin resins, polyethylene is preferred.

[0118] The adhesive layer of the protective film preferably contains 80% by weight or more of an elastomer or thermoplastic resin, more preferably 90% by weight or more of an elastomer or thermoplastic resin, and further preferably 95% by weight or more of an elastomer or thermoplastic resin, based on the total weight of the adhesive layer.

[0119] In the antiglare laminate, the thickness of the protective film is preferably 10 μm to 100 μm, and more preferably 20 μm to 80 μm.

[0120] Example

[0121] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the present invention is not limited to the following Examples, and can be implemented with arbitrary modifications within the scope of the present invention.

[0122] <SW hardness>

[0123] On the surface of the anti-glare layer, #0000 steel wool is placed at 100 gf / cm 2 The scratch was made by reciprocating 15 times under the pressure of . The degree of damage was visually observed and evaluated on a 10-grade scale, with RANK1 to RANK10.

[0124] RANK1: No scratches (same as inorganic glass);

[0125] RANK2: 1 to 5 scars;

[0126] RANK3: 6 to 10 scars;

[0127] RANK4: 11 to 15 scars;

[0128] RANK5: 16-20 scars;

[0129] RANK6: 21 to 25 scars;

[0130] RANK7: 26-30 scars;

[0131] RANK8: 31-40 scars;

[0132] RANK9: more than 41 scars (same as polymethacrylic acid);

[0133] RANK10: 41 or more scratches (same as polycarbonate).

[0134] <Pencil hardness>

[0135] The measurement was performed based on the conditions of JIS K 5600-5-4: 1999, and the number of the hardest pencil that did not leave a scratch was defined as the pencil hardness.

[0136] <Fitness test>

[0137] Evaluation was performed using the evaluation method of JIS K5600-5-6: 1999. Examples and comparative examples with evaluation results classified as 0 were evaluated as "good" in terms of adhesion, and Examples and comparative examples with evaluation results classified as 1 to 5 were evaluated as "poor" in terms of adhesion.

[0138] <Heating test>

[0139] After the anti-glare laminate was immersed in boiling water for 30 minutes, the appearance was visually evaluated. Examples and comparative examples without changes were evaluated as "good", and Examples and comparative examples with changes were evaluated as "poor".

[0140] <Haze>

[0141] Evaluation was performed using a haze meter "HM-150" manufactured by Murakami Color Co., Ltd. in accordance with JIS K7136:2000.

[0142] <Ten-point average roughness Rzjis>

[0143] The surface roughness was evaluated under the following conditions based on JIS B 0601-2001 using a surface roughness measuring machine "SURFTEST SJ-210" manufactured by Mitutoyo Corporation.

[0144] Reference length: 0.8mm;

[0145] Evaluation length: 5 times the reference length;

[0146] Feed speed of the stylus: 0.5 mm / s.

[0147] <Oil absorption>

[0148] The measurement was conducted in accordance with JIS K5101 using "Linseed Oil" manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.

[0149] <Glare>

[0150] The anti-glare laminate was placed on an iPad 6 with 265 ppi displaying green (R: 29, G: 205, B: 0) with the anti-glare layer facing upward, and the degree of glare was visually observed and evaluated according to the following criteria.

[0151] A: Almost no glare;

[0152] B: Glare is visible but does not affect practicality;

[0153] C: Visible glare that affects practicality.

[0154] Preparation Example 1

[0155] 50% by mass of DPE-6A (monomer containing hexafunctional acryloyl groups, manufactured by Kyoeisha Chemical Co., Ltd.), 50% by mass of SMP-220A (polymer containing acryloyl groups, double bond equivalent of 220 g / mol, manufactured by Kyoeisha Chemical Co., Ltd.), 3% by mass of Omnirad184 (photopolymerization initiator, manufactured by IGM Resins BV), and 7% by mass of SYLYSIA430 (silicon dioxide particles, average particle size of 4.1 μm, oil absorption of 230 mL / 100 g, manufactured by Fuji Silicon Chemical Co., Ltd.) were diluted with propylene glycol monoethyl ether to a solid content concentration of 40%, and stirred for 10 minutes using a homogenizer to obtain a mixed solution.

[0156] (Example 1)

[0157] As a substrate, DF02U (manufactured by Mitsubishi Gas Chemical Co., Ltd., thickness 0.180 mm) which is a double-layer product of bisphenol A polycarbonate and PMMA was used, and the mixed solution obtained in Preparation Example 1 was applied to the PMMA side using a bar coater so that the film thickness after drying was 10 μm, and then dried in an oven at 70° C. for 2 minutes. Thereafter, UV curing was performed in a nitrogen atmosphere using a UV irradiator manufactured by Heraeus AG so that the cumulative light amount was 400 mJ, thereby obtaining an anti-glare laminate.

[0158] (Example 2)

[0159] An anti-glare laminate was produced in the same manner as in Example 1 except that SYLYSIA550 (silicon dioxide particles, average particle size 3.9 μm, oil absorption 160 mL / 100 g, manufactured by Fuji Silicon Chemical Co., Ltd.) was used instead of SYLYSIA430 of Preparation Example 1.

[0160] (Example 3)

[0161] An anti-glare laminate was produced in the same manner as in Example 1 except that SYLYSIA 730 (silicon dioxide particles, average particle size 4.0 μm, oil absorption 95 mL / 100 g, manufactured by Fuji Silicon Chemical Co., Ltd.) was used instead of SYLYSIA 430 in Preparation Example 1.

[0162] (Example 4)

[0163] An anti-glare laminate was produced in the same manner as in Example 1 except that SYLOPHOBIC 200 (silicon dioxide particles, average particle size 3.9 μm, oil absorption 230 mL / 100 g, manufactured by Fuji Silysia Chemical Co., Ltd.) was used instead of SYLYSIA 430 in Preparation Example 1.

[0164] (Example 5)

[0165] An anti-glare laminate was produced in the same manner as in Example 1 except that 20SM-C11 (silica particles, average particle size 2.0 μm, oil absorption 35 mL / 100 g, manufactured by Admatechs) was used instead of SYLYSIA 430 in Preparation Example 1.

[0166] (Example 6)

[0167] An anti-glare laminate was produced in the same manner as in Example 1 except that DPE-6A of Preparation Example 1 was changed to 70 mass %, SMP-220A was changed to 30 mass %, and SYLYSIA 550 was used instead of SYLYSIA 430.

[0168] (Example 7)

[0169] An anti-glare laminate was produced in the same manner as in Example 1 except that SMP-250A (acryloyl group-containing polymer, double bond equivalent 360 g / mol, manufactured by Kyoeisha Chemical Co., Ltd.) was used instead of SMP-220A in Preparation Example 1, and SYLYSIA550 was used instead of SYLYSIA430.

[0170] (Example 8)

[0171] An anti-glare laminate was produced in the same manner as in Example 1 except that SMP-360A (acryloyl group-containing polymer, double bond equivalent 360 g / mol, manufactured by Kyoeisha Chemical Co., Ltd.) was used instead of SMP-220A in Preparation Example 1, and SYLYSIA550 was used instead of SYLYSIA430.

[0172] (Example 9)

[0173] An anti-glare laminate was produced in the same manner as in Example 1 except that PE-3A (trifunctional acryloyl group-containing monomer, manufactured by Kyoeisha Chemical Co., Ltd.) was used instead of DPE-6A in Preparation Example 1, and SYLYSIA 550 was used instead of SYLYSIA 430.

[0174] (Comparative Example 1)

[0175] An anti-glare laminate was produced in the same manner as in Example 1 except that SYLYSIA350 (silicon dioxide particles, average particle size 3.9 μm, oil absorption 320 mL / 100 g, manufactured by Fuji Silicon Chemical Co., Ltd.) was used instead of SYLYSIA430 of Preparation Example 1.

[0176] (Comparative Example 2)

[0177] An antiglare laminate was produced in the same manner as in Example 1 except that Sunsphere H-33 (silica particles, average particle size 3.0 μm, oil absorption 400 mL / 100 g, manufactured by AGC Si-Tech Co., Ltd.) was used instead of SYLYSIA 430 of Preparation Example 1.

[0178] (Comparative Example 3)

[0179] An anti-glare laminate was produced in the same manner as in Example 1 except that Nipsil E-1011 (silica particles, average particle size 4.2 μm, oil absorption 350 mL / 100 g, manufactured by Tosoh Silicone Co., Ltd.) was used instead of SYLYSIA 430 in Preparation Example 1.

[0180] (Comparative Example 4)

[0181] An anti-glare laminate was produced in the same manner as in Example 1 except that Nipsil E-1009 (silica particles, average particle size 5.6 μm, oil absorption 350 mL / 100 g, manufactured by Tosoh Silicone Co., Ltd.) was used instead of SYLYSIA 430 in Preparation Example 1.

[0182] The evaluation results of the anti-glare laminated bodies obtained in Examples 1 to 9 and Comparative Examples 1 to 4 are shown in Tables 1 and 2 below.

[0183]

Table 1

[0184]

[0185]

Table 2

[0186]

Claims

1. An anti-glare laminate, characterized in that: At least comprising a substrate layer and an anti-glare layer, The haze H of the anti-glare laminate and the ten-point average roughness Rzjis of the anti-glare layer measured with a reference length of 0.8 mm satisfy the following formula (1): H / Rzjis≥4.0 (1).

2. The anti-glare laminate according to claim 1, wherein: The anti-glare laminate has a haze of 1 to 20%.

3. The anti-glare laminate according to claim 1 or 2, wherein: The anti-glare layer has a ten-point average roughness Rzjis of 0.2 to 1.5 μm when the reference length is set to 0.8 mm.

4. The anti-glare laminate according to any one of claims 1 to 3, wherein: The antiglare layer contains an active energy ray-curable resin and light diffusing fine particles.

5. The anti-glare laminate according to any one of claims 1 to 4, wherein: The anti-glare layer contains at least a monomer A containing a multifunctional (meth)acryloyl group, a polymer B containing a (meth)acryloyl group, a photopolymerization initiator C and silica particles D, the average particle size of the silica particles is 1 to 7 μm, and the oil absorption of the silica particles is 30 to 250 mL / 100 g.

6. The anti-glare laminate according to claim 5, wherein: When the total of the components A and B is 100 mass %, the proportion of the component A is 40 to 90 mass %, the proportion of the component B is 10 to 60 mass %, the double bond equivalent of the component B is 400 g / mol or less, and the weight average molecular weight of the component B is 5,000 to 100,000.

7. The anti-glare laminate according to claim 5, wherein: When the total of the above-mentioned component A and component B is 100% by mass, the content of the component D is 1 to 20% by mass.

8. The anti-glare laminate according to any one of claims 1 to 7, wherein: The substrate layer includes an aromatic polycarbonate resin layer.

9. The anti-glare laminate according to any one of claims 1 to 8, wherein: The substrate layer includes at least two layers of an acrylic resin layer and an aromatic polycarbonate resin layer.

10. The anti-glare laminate according to any one of claims 1 to 9, wherein: The anti-glare layer is provided with an optical interference layer.

11. The anti-glare laminate according to any one of claims 1 to 10, wherein: The substrate layer has an adhesive layer on the surface opposite to the anti-glare layer.

Citation Information

Patent Citations

  • Anti-static and Anti-glare hard coat film and its production process

    JP2009066891A